2011
DOI: 10.1111/j.1749-4877.2011.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of an old endemic murid rodent of Australia, the Spinifex hopping mouse, Notomys alexis: adaptations for life in the arid zone

Abstract: The Spinifex hopping mouse (Notomys alexis Thomas, 1922) is an arid adapted Australo-Papuan old endemic rodent that undergoes boom and bust population cycles. In this communication, we review our findings on the timing of reproduction and the potential reproductive rate of this species. To investigate the first question, the reproductive condition of adult females, and occurrence of immatures, in a population on a cattle station in central Australia was determined and, for the second, data from a laboratory co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…The integral role of water as a reproductive cue for desert-rodents has also been demonstrated in water-supplementation studies ( reviewed in [45, 50]) as well as research on the effects of desert rainfall [5154]. Thus, Schwimmer and Haim [46] asserted that reproductive timing is the most evolutionarily important adaptation for desert rodents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The integral role of water as a reproductive cue for desert-rodents has also been demonstrated in water-supplementation studies ( reviewed in [45, 50]) as well as research on the effects of desert rainfall [5154]. Thus, Schwimmer and Haim [46] asserted that reproductive timing is the most evolutionarily important adaptation for desert rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, water-supplementation studies among wild desert rodents resulted in prolonged breeding seasons in the hairy-footed gerbil and the four-striped grass mouse, but not in the Cape short-eared gerbil [50]. Recent research has confirmed the importance of rainfall as a reproductive cue in the Arabian spiny mouse [51], the Baluchistan gerbil [52], Chessman’s gerbil [53] and the Spinifex hopping mouse [54]. The focus of this previous research was to investigate reproductive cues and consequences of water-limitation in desert rodents, namely how species have adapted breeding onset and cessation patterns to respond to water availability.…”
Section: Introductionmentioning
confidence: 99%
“…The integral role of water as a reproductive cue for desert-rodents has also been demonstrated in water-supplementation studies (reviewed in [45,50]) as well as research on the effects of desert rainfall [51][52][53][54]. Thus, Schwimmer and Haim [46] asserted that reproductive timing is the most evolutionarily important adaptation for desert rodents.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, watersupplementation studies among wild desert rodents resulted in prolonged breeding seasons in the hairyfooted gerbil and the four-striped grass mouse, but not in the Cape short-eared gerbil [50]. Recent research has confirmed the importance of rainfall as a reproductive cue in the Arabian spiny mouse [51], the Baluchistan gerbil [52], Chessman's gerbil [53] and the Spinifex hopping mouse [54]. The focus of this previous research was to investigate reproductive cues and consequences of water-limitation in desert rodents, namely how species have adapted breeding onset and cessation patterns to respond to water availability.…”
Section: Introductionmentioning
confidence: 99%
“…The articles by Gorini et al (2011) and Pederson et al (2011) both investigate the reaction of voles to different environmental scenarios in Scandinavia: the former looking at the field vole relationship with changes in habitat, specifically the impact of forestry on the mammalian communities in Fennoscandian boreal forests, and the latter considering root voles' preference for bilberry along gradients of simulated moose density and site productivity. The paper by Bennett (2011) reviews socially-induced infertility in Southern African Damaraland mole-rats, while Breed and Leigh (2011) investigate the reproductive biology of another arid adapted endemic rodent, the Spinifex hopping mouse of Australia. Wang et al (2011) discuss the behavioral and physiological responses of striped field mice to predator odor, while Xu et al (2011) report a loss of cellular and humoral immunity in overweight Mongolian gerbils; both studies in Asia.…”
Section: Recent Progress In Rodent Biology and Management Editorialmentioning
confidence: 99%